Microexclusion in Inclusive Mathematics Education - Jark, Paulo C. [UNESP]; Raposo-Ferreira, Talita M. M. [UNESP]; Terra, Erika M. [UNESP]; Matiz, Oscar R. Sierra[UNESP]; Anai, Letícia A. [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Tinucci-Costa, Mirela [UNESP]; Laufer-Amorim, Renee [UNESP]; De Nardi, Andrigo B. [UNESP] (Springer Nature, 2019)
In Brazil, the right of all students to education is legally reinforced in order to make educational institutions truly inclusive. However, in inclusive contexts, the processes of exclusion, which previously were explicit, have often been transformed into local and implicit actions. Such microexclusions may be carried out covertly, which makes it difficult to identify and denounce them. In particular, we investigate what types of microexclusions can be identified in inclusive contexts. In so doing, we present a range of cases of microexclusions, which illustrates that overall processes of macroinclusions can be accompanied by microexclusions. This applies to any educational context, including inclusive mathematics education. We identify eight different types of microexclusions having to do with ignoring, normalising, paying special attention to, barring, labelling, disqualification, stigmatising and institutionalising.
Keywords: Inclusive education; Macroinclusion; Mathematics education; Microexclusion; Types of microexclusions